Europium Doped Silicon Quantum Dot As a Novel FRET Based Dual Detection Probe: Sensitive Detection of Tetracycline, Zinc, and Cadmium. Issue 10 (2nd September 2021) - Zhou, Jialing; Zhao, Ruoxi; Liu, Shikai; Feng, lili; Li, Wenting; He, Fei; Gai, Shili; Yang, Piaoping
Abstract: The imbalance of Zn 2+ /Cd 2+ in the human body can lead to many serious diseases due to the overuse of antibiotics and deposition in animal products. Developing a functional material for detecting is challenging and in demand. Herein, silicon quantum dots (SiQDs) are designed as a functional platform for the detection of tetracycline and Zn 2+ /Cd 2+ . The COOH functionalized SiQDs with the emission wavelength of 450 nm are chelated with Eu(NO3 )3 to form SiQDs‐Eu 3+ ratio fluorescent probes, which can be used to detect tetracycline (TCs) and Zn 2+ /Cd 2+ by fluorescence resonance energy transfer (FRET) principle sequentially. The fluorescent probe showed good linearity between ion concentration and fluorescence enhancement. The detection limit of TCs and Zn 2+ /Cd 2+ are 0.2 × 10 −6 m and 3 × 10 −6 m, respectively, when the pH of the solution is 7.4. In addition, the synthesized SiQDs‐Eu 3+ exhibited good stability (from 94.9% to 103.1%). The relative standard deviations (RSD, n = 10) of human serum and urine were both less than 3%. Therefore, the SiQDs‐Eu 3+ ratio fluorescence probe will provide a good application prospect in actual sample detection. Abstract : A new type of silicon quantum dots (SiQDs) with thioglycolic acid capping is prepared. After their chelation with Eu 3+, the fluorescence at 450 and 616 nm is modulated by the fluorescence resonance energy transfer mechanism under the excitation of UV light at 370 nm. This enables the specific detection of tetracycline and Zn 2+ /Cd 2+ in human serum and urine samples.